Polycystin-2 mediates mechanical tension-induced osteogenic differentiation of human adipose-derived stem cells by activating transcriptional co-activator with PDZ-binding motif - Wang, Liang; Lu, Yahui; Cai, Guanhui; Chen, Hongyu; Li, Gen; Liu, Luwei; Sun, Lian; Guan, Zhaolan; Sun, Wen; Zhao, Chunyang; Wang, Hua (Frontiers in Physiology, 2022)
Human adipose-derived stem cells (hASCs) have multi-directional differentiation potential including osteogenic differentiation. Mechanical stimulation is thought to be a key regulator of bone remodeling and has been proved to promote osteogenic differentiation of mesenchymal stem cells. However, the mechanism how mechanical tension-induced osteogenesis of hASCs still remains poor understood. Polycystin-2 (PC2), a member of the transient receptor potential polycystic (TRPP) family, is involved in cilia-mediated mechanical transduction. To understand the role of PC2 in osteogenic differentiation under mechanical stimuli in hASCs, PKD2 gene was stably silenced by using lentivirus-mediated shRNA technology. The results showed that mechanical tension sufficiently enhanced osteogenic differentiation but hardly affected proliferation of hASCs. Silencing PKD2 gene caused hASCs to lose the ability of sensing mechanical stimuli and subsequently promoting osteogenesis. PC2 knock-out also reduced the cilia population frequency and cilia length in hASCs. TAZ (transcriptional coactivator with PDZ-binding motif, also known as Wwtr1) could mediate the genes regulation and biological functions of mechanotransduction signal pathway. Here, mechanical tension also enhanced TAZ nuclear translocation of hASCs. PC2 knock-out blocked tension‐induced upregulation of nuclear TAZ and suppress tension‐induced osteogenesis. TAZ could directly interact with Runx2, and inhibiting TAZ could suppress tension‐induced upregulation of Runx2 expression. In summary, our findings demonstrated that PC2 mediate mechanical tension-induced osteogenic differentiation of hASCs by activating TAZ.